COVID‐19 research: an opinion piece. Issue 8 (21st July 2020) - Waters, L; Rockstroh, JK
Abstract : The unprecedented global scale of COVID‐19 globally has triggered a race to discover interventions to reduce associated morbidity and mortality and rapid release of research findings prior to any degree of critical review. As with previous novel infection outbreaks, antiretrovirals are just one drug class that has been held up as a potential strategy for prophylaxis and treatment with scant evidence and risk of harm. Here we summarize the evidence for antiretrovirals to treat COVID‐19 and, as a drug that has also been studied in HIV, hydroxychloroquine, and flag some of the pitfalls of using therapies that have not been evaluated robustly.